2012
DOI: 10.1177/1934578x1200700531
|View full text |Cite
|
Sign up to set email alerts
|

The Composition and Antimicrobial Activities of Cyperus conglomeratus, Desmos chinensis var. lawii and Cyathocalyx zeylanicus Essential Oils

Abstract: The essential oil compositions of the rhizomes of Cyperus conglomeratus (Cyperaceae) collected from Oman and the leaves of two Annonaceae plants, Desmos chinensis var. lawii and Cyathocalyx zeylanicus collected from India were studied by GC, GC-MS and 13 C NMR spectroscopy. Twenty-six compounds, representing 84.4% of the oil were identified in C. conglomeratus, where eugenol (31.3%), α-cyperone (10.5%) and cyperotundone (8.4%) were the major compounds. Twelve compounds, constituting 100%, were identified in D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The antioxidant capacity of C. conglomeratus and C. capitatus can be attributed to the high content of bioactive compounds [9,41]. Moreover, C. conglomeratus is characterized by various biological activities such as anthelmintic, antidiarrheal, antidiabetic [41,42], antioxidant, antimicrobial [34,43], and cytotoxic activity [9]. On the other hand, P. turgidum has been reported to possess anti-inflammatory, antibacterial, antihepatotoxic, antifungal, and cytotoxic activities [44][45][46][47][48].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The antioxidant capacity of C. conglomeratus and C. capitatus can be attributed to the high content of bioactive compounds [9,41]. Moreover, C. conglomeratus is characterized by various biological activities such as anthelmintic, antidiarrheal, antidiabetic [41,42], antioxidant, antimicrobial [34,43], and cytotoxic activity [9]. On the other hand, P. turgidum has been reported to possess anti-inflammatory, antibacterial, antihepatotoxic, antifungal, and cytotoxic activities [44][45][46][47][48].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…(E, E)-α-farnesene (2.6%), and germacrene B (2.4%). In comparison to the previous study (Hisham et al, 2012), analyses of the leaf oil of Cyathocalyx zeylanicus has successfully identified thirty-two compounds, comprising 98.0% of total oil. The essential oil was reported to show high amounts of β-caryophyllene (21.6%), α-pinene (20.4%) and (E)β-ocimene (11.8%).…”
Section: Resultsmentioning
confidence: 78%
“…However, there is little information about the chemical composition and the biological properties of the essential oil of the genus Cyathocalyx. Previous study on the essential oil of Cyathocalyx have been reported on Cyathocalyx zeylanicus collected from India (Hisham et al, 2012). In continuation of our systematic studies on pharmacologically active volatiles from Malaysian plants (Salleh et al,2014(Salleh et al, , 2015a(Salleh et al, , 2015b(Salleh et al, , 2016a(Salleh et al, , 2016b, we describe in this paper an evaluation of the chemical composition and acetylcholinesterase inhibitory activity of the essential oil from the leaf of C. pruniferus.…”
Section: Introductionmentioning
confidence: 77%
“…This herb is important in traditional medicine as an emollient, diuretic, analgesic, anthelmintic, and for treating thoracic diseases. Previous studies have described the biological activities of this plant, such as antiulcer activity, antimicrobial activity [8,9], antioxidant and antidiarrheal activities [10], and wound healing activity [11]. In previous phytochemical investigations of C. conglomeratus, several components of different classes were isolated, including essential oil [12], flavonoids [13,14], stilbenes [15], steroids, and triterpene [8].…”
Section: Introductionmentioning
confidence: 99%